Effects of High White and Brown Sugar Consumption on Serum Level of Brain-Derived Neurotrophic Factor, Insulin Resistance, and Body Weight in Albino Rats - Shamsi-Goushki, Ali (J Obes Metab Syndr, 2020)
BACKGROUND: In recent decades, consumption of simple sugars has increased dramatically, which contributes to health problems including insulin resistance and obesity. In this study, we investigated the effects of high concentrations of white sugar (WS) and brown sugar (BS) on serum concentration of brain-derived neurotrophic factor (BDNF), insulin resistance, and body weight in albino rats. METHODS: Twenty-four male Wistar rats were randomly divided into three groups: control, a group treated with 15% WS, and a group treated with 15% BS. Rats were given WS and BS by gavage (daily) for 42 days. At the end of the intervention period, serum level of BDNF, insulin resistance, and body weight were measured. RESULTS: Body weight and insulin resistance were significantly increased and serum BDNF level was decreased in both WS and BS groups compared to the control group (P<0.05). In the WS-treated rats, the amount of changes in the insulin resistance, body weight, and serum BDNF level was greater compared to that in BS-treated (P<0.05). CONCLUSION: Due to the adverse effects of consuming high levels of WS and BS on serum level of BDNF, insulin resistance, and body weight, high intakes of these sweeteners are not recommended.